Concussion history associated with increased postural control deficits after subsequent injury. (20th February 2019) - Murray, N G; Szekely, B; Moran, R; Ryan, G; Powell, D; Munkasy, B A; Buckley, T A; Guskiewicz, K
Abstract: Objective : Postural control deficits have been extensively reported following sport-related concussions. Concussed athletes demonstrate these deficits as early as 24 h post-concussion and may persist for up to six months. Many of these prior studies have included mixed samples with prior injury history that may affect the postural control data. The purpose of this investigation was to evaluate the effect of concussion history on postural control 24–48 h following sport-related concussion in Division I athletes. Approach : Twenty-eight Division I athletes (seven athlete controls (CON), seven no history (SRC0), seven with a previous concussion (SRC1), and seven with 2–3 concussions (SRC3) participated in this study. All participants were assessed within 24–48 h post-subsequent SRC and performed three trials of quiet stance in the eyes closed (EC) conditions for 30 s each on a force platform (1000 Hz). The data were analyzed with root mean square (RMS) and mean excursion velocity (MEV) in the anteroposterior (AP) and mediolateral (ML) directions. Two 3  ×  2 MANOVAs were run by direction for group comparisons. Main results : SRC2 had significantly greater RMS than CON, SRC0, and SRC1 in the AP direction and ML direction. SRC2 exhibited significantly greater AP and ML MEV than CON, SRC0, and SRC1. Significance : These results demonstrate that having 2–3 prior concussions negatively affects the postural system after a subsequent head injury. Sports medicine staff should approach the recovery process with caution with those that have a prior history of concussion, due to the negative effects that history of concussion has on postural control strategies.